Innovative Therapeutic Approaches for Huntington’s Disease: From Nucleic Acids to GPCR-Targeting Small Molecules - Komatsu, Hidetoshi (Frontiers in Cellular Neuroscience, 2021)
Huntington’s disease (HD) is a fatal neurodegenerative disorder due to an extraordinarily expanded CAG repeat in the huntingtin gene that confers a gain-of-toxic function in the mutant protein. There is currently no effective cure that attenuates progression and severity of the disease. Since HD is an inherited monogenic disorder, lowering the mutant huntingtin (mHTT) represents a promising therapeutic strategy. Huntingtin lowering strategies mostly focus on nucleic acid approaches, such as small interfering RNAs (siRNAs) and antisense oligonucleotides (ASOs). While these approaches seem to be effective, the drug delivery to the brain poses a great challenge and requires direct injection into the central nervous system (CNS) that results in substantial burden for patients. This review discusses the topics on Huntingtin lowering strategies with clinical trials in patients already underway and introduce an innovative approach that has the potential to deter the disease progression through the inhibition of GPR52, a striatal-enriched class A orphan G protein-coupled receptor (GPCR). GPCRs have emerged as the most potential targets for the treatment of CNS diseases. Chemically simple, potent, and selective GPR52 antagonists have been discovered through high-throughput screening and subsequent structure-activity relationship studies. These small molecule antagonists not only diminish both soluble and aggregated mHTT in the striatum, but also ameliorate HD-like defects in HD mice. This therapeutic approach offers great promise as a novel strategy for HD therapy, while nucleic acid delivery still faces considerable challenges.